MRSM Betong Outing System - ANAK SYLVESTER BELIANG, ABBY DANDU; BINTI ZAINAL, DR. NUREZAYANA (Applied Information Technology And Computer Science, 2025)
This project addresses the need for an efficient outing management system within an educational institution. Faced with challenges in manual record-keeping and coordination, the study aims to develop a comprehensive solution. Objectives include designing a user-friendly interface for students, parents, and dormitory staff, implementing a secure QR code system for tracking entry and exit times, and establishing transparent communication channels along with location tracking. The study utilizes standard software development methodologies, incorporating use case modeling. Key findings reveal enhanced efficiency, transparency, and security in outing management. The discussion emphasizes the system's positive impact and suggests future enhancements, focusing on continual improvement and user feedback integration.